Synergetic effect of electroconvulsive therapy and clozapine therapy in treating severe intractable aggressive behaviour in an adult with intellectual disability: a case report / Wei Da Son, Muhammad Adib Baharom and Suthahar Ariaratnam - Son, Wei Da; Baharom, Muhammad Adib; Ariaratnam, Suthahar (Faculty of Medicine, 2024)
There is scarce literature on the use of either clozapine or Electroconvulsive therapy (ECT) and/or their combination in patients having intellectual disability with aggression. To the best of our knowledge, we report the first case of combination use of ECT and clozapine in treating severe intractable aggressive behaviour in a 19-year-old male of Chinese descent with severe intellectual disability. Patient presented with disturbed sleep pattern, self-injurious, and severe aggressive behaviour soon after the announcement of Movement Control Order (MCO) by the government of Malaysia sometime in March 2020 as preventive measure to contain COVID19 spread. Consequently, patient's daily routine was affected, and he had to stay home. Psychosocial interventions were attempted by family members. However, the challenging behaviour persisted for 3 months which led to caregiver burnout and subsequent admission. During the hospitalisation, occupational therapy was initiated, and medication treatment was optimised. Blood parameters investigation was unremarkable. The aggressive behaviours were assessed using modified overt aggression scale (MOAS) and brief psychiatry rating scale (BPRS). There was no satisfactory improvement noted despite being on three secondgeneration antipsychotics (Olanzapine, Quetiapine and Amisulpride). Later, concurrent use of clozapine and ECT were initiated. Patient's improvement was satisfactory, and he was discharged with Clozapine at 200mg daily as well as after completing 14 sessions of bitemporal ECT (Thymatron system IV, Illinois, USA), thrice a week with 0.5 millisecond pulse width, 70Hz and titration between 25-508 milliCoulombs (mC). The combination use of ECT with clozapine appeared to have a both synergetic and efficacious effects in treating intellectual disability with aggressive behaviours.